2022
DOI: 10.1038/s41598-022-11401-7
|View full text |Cite
|
Sign up to set email alerts
|

Progressive compressive sensing of large images with multiscale deep learning reconstruction

Abstract: Compressive sensing (CS) is a sub-Nyquist sampling framework that has been employed to improve the performance of numerous imaging applications during the last 15 years. Yet, its application for large and high-resolution imaging remains challenging in terms of the computation and acquisition effort involved. Often, low-resolution imaging is sufficient for most of the considered tasks and only a fraction of cases demand high resolution, but the problem is that the user does not know in advance when high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…3 and 4, the extent of dependency on the Gaussian and quantization noise depends on the CI method and compression ratio. In general, CMS-Net [11] outperforms the other methods provided that the sensing is done with at least 8 bits. In such a case it exhibits the best performance for SNRs higher than 30dB at 10% compression ratio, and at CR=1% with SNRs higher than 15 dB.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3 and 4, the extent of dependency on the Gaussian and quantization noise depends on the CI method and compression ratio. In general, CMS-Net [11] outperforms the other methods provided that the sensing is done with at least 8 bits. In such a case it exhibits the best performance for SNRs higher than 30dB at 10% compression ratio, and at CR=1% with SNRs higher than 15 dB.…”
Section: Discussionmentioning
confidence: 93%
“…Out of its four versions, we tested AMP_Net_K, over 6 phases and 9 phases. [11]. This model uses the Hadamard transform by taking the smallest block transformed, from the transformed image, reconstructing it, and adding the reconstruction to the bigger block in size until we receive the reconstructed image.…”
Section: Tested Modelsmentioning
confidence: 99%
“…24,25 Recently, machine learning methods have also been proposed for finding the CS reconstruction. 26,27 Next, we outline the OMP algorithm. In a minimum L 1 norm solution using linear programming (LP), we seek:…”
Section: Theorymentioning
confidence: 99%
“…These patterns under-sample the target's optical properties for image reconstruction, recognition, and assessment, albeit at the price of information loss. Recently, it has been shown that artificial intelligence (AI) and machine learning can be employed to process compressed data, where the quality of the reconstructed image is improved by deep learning and recurrent neural networks [28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%